A novel consensus bacterial 6-phytase variant improves the responses of laying hens fed an inorganic phosphorus-free diet with reduced energy and nutrients from 23 to 72 wk of age - Moura, Thaila F. [UNESP] (2023)
The objective of this study was to evaluate the effect of a novel consensus bacterial 6-phytase variant (PhyG) on egg productivity, eggshell quality, and body composition of laying hens fed inorganic phosphate-free diets with reduced energy and nutrients from 23 to 72 wk of age. Five treatments were randomly assigned, performing 28 replicates per treatment with 4 hens each, totaling 560 Hy-Line W80 birds. A positive control (PC) feed was formulated to contain adequate levels of energy and nutrients. A negative control (NC) feed was formulated without added inorganic phosphate (0.12% nonphytic phosphorus [nPP]) and reduced in Ca, Na, dig AA, and metabolizable energy in comparison with PC feed. Phytase was supplemented in the NC feed at 0, 300, 600, and 900 FTU/kg of feed. The responses evaluated were performance, egg quality, economic analysis, body composition, and tibia composition. Data were analyzed by a 2-factor (diet and age) repeated measure analysis. Overall, the feed intake, hen-day egg production, egg mass, and egg revenue were reduced by the complete removal of dicalcium phosphate (DCP) (P < 0.05). Supplement phytase in the NC diet elicits a positive response on each one of those variables. Laying hens consuming the NC feed with 900 FTU/kg of phytase produced more eggs per hen-housed compared with the phytase dosages of 300 and 600 FTU/kg. Body composition was not affected by dietary nPP, Ca, Na, dig AA, and energy reductions (P > 0.05). At 72-wk-old, tibia ash was reduced in hens consuming the NC diet vs. PC (P < 0.05) and no difference was observed between hens supplemented with phytase and the PC feed. Margin over feeding cost increased in a dose-dependent manner with phytase supplementation. Supplementation with 900 FTU/kg of phytase is recommended to improve the number of eggs produced per hen-housed and the number of marketable eggs produced through 23 to 72 wk of age, under this dietary setting.